Latent profile analysis of depression and anxiety comorbidity in patients with acute ischemic stroke: a prospective study - Chen, Dongli; Zhang, Hong; Xiu, Yuqi; Xiao, Chunxun; Liu, Zhili; Lin, Hongchun; Zheng, Shaoyan; Wu, Yanchun (Frontiers in Psychiatry, 2025)
IntroductionStroke is a leading cause of mortality and disability globally, with post-stroke depression and post-stroke anxiety being common and significant complications that hinder recovery and adversely affect quality of life. Although these conditions frequently co-occur, their heterogeneity remains poorly understood. This study integrates the Health Ecology Model (HEM) and employs Latent Profile Analysis (LPA) to identify distinct psychological profiles of depression and anxiety among patients with acute ischemic stroke (AIS), as well as to investigate their multilevel determinants.MethodsPatients with AIS from a tertiary hospital in Guangdong Province, China, from January to November 2024 were included. Within one week of stroke onset, the data of sociodemographic, clinical characteristics, swallowing function, stroke severity, activities of daily living, resilience and social support were collected according to the HEM guidelines. The Patient Health Questionnaire-9 and the Generalized Anxiety Disorder-7 were used to assess the depression and anxiety symptoms of the patients three months after stroke onset. LPA was employed to identify distinct psychological profiles, and variables with a P < 0.1 in the univariate analysis were retained for inclusion in the subsequent multivariate analysis.ResultsA total of 551 patients with AIS were included in the study, 49 were lost to follow-up or withdrew, resulting in a final analytic sample of 502 participants (91.11%). Three distinct psychological profiles were identified: no depression-anxiety (67.93%), high-risk depression-anxiety (21.12%) and major depression-anxiety (10.95%). In the multivariate analysis, the results indicated that occupation (OR = 0.61, 95% CI [0.40–0.93]), National Institutes of Health Stroke Scale (NIHSS, OR = 1.60, 95% CI [1.06–2.42]), Barthel Index (BI, OR = 1.67, 95% CI [1.27–2.19]) and hypertension (OR = 2.37, 95% CI [1.29–4.35]) were independent predictors of the high-risk depression-anxiety profile, while NIHSS (OR = 2.33, 95% CI [1.42–3.85]), BI (OR = 2.65, 95% CI [1.62–4.35]) and resilience (OR = 0.92, 95% CI [0.87–0.98]) were significantly associated with the major depression-anxiety profile.ConclusionsThis study reveals significant heterogeneity in psychological distress among AIS survivors. Key predictors of post-stroke emotional comorbidity include occupation, hypertension, stroke severity, activities of daily living and low resilience. Early identification of high-risk individuals can significantly enhance screening and intervention strategies, particularly by focusing on symptoms such as anhedonia and nervousness. Future research should focus on longitudinal designs and objective biomarkers to better understand the mechanisms behind post-stroke emotional comorbidity.